2020
DOI: 10.1186/s12864-020-6600-6
|View full text |Cite
|
Sign up to set email alerts
|

Stress-mediated convergence of splicing landscapes in male and female rock doves

Abstract: Background: The process of alternative splicing provides a unique mechanism by which eukaryotes are able to produce numerous protein products from the same gene. Heightened variability in the proteome has been thought to potentiate increased behavioral complexity and response flexibility to environmental stimuli, thus contributing to more refined traits on which natural and sexual selection can act. While it has been long known that various forms of environmental stress can negatively affect sexual behavior an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…Growing evidence suggests that alternative splicing is an important axis of transcriptional variation contributing to phenotypic plasticity (Marden 2008 ; Verta and Jacobs 2022 ; Wright et al 2022 ). Large transcriptome-wide splicing differences between plastic phenotypes have recently been uncovered in a wide array of non-model species (Aamodt 2008 ; Grantham and Brisson 2018 ; Healy and Schulte 2019 ; Martin Anduaga et al 2019 ; Lang et al 2020 ; Thorstensen et al 2021 ; Steward et al 2022 ; Tian and Monteiro 2022 ). Differential splicing between plastic phenotypes is an important complement to whole-gene expression variation because it increases transcriptional complexity, control, and flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence suggests that alternative splicing is an important axis of transcriptional variation contributing to phenotypic plasticity (Marden 2008 ; Verta and Jacobs 2022 ; Wright et al 2022 ). Large transcriptome-wide splicing differences between plastic phenotypes have recently been uncovered in a wide array of non-model species (Aamodt 2008 ; Grantham and Brisson 2018 ; Healy and Schulte 2019 ; Martin Anduaga et al 2019 ; Lang et al 2020 ; Thorstensen et al 2021 ; Steward et al 2022 ; Tian and Monteiro 2022 ). Differential splicing between plastic phenotypes is an important complement to whole-gene expression variation because it increases transcriptional complexity, control, and flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies on AS have been reported in relation to bird reproduction ( Zhao et al, 2007 ; Huang et al, 2012 ; Lang et al, 2020 ; Rogers et al, 2021 , Sun et al, 2021 ). AS of testis-specific lactate dehydrogenase C ( LDHC ) and doublesex- and mab-3-related transcription factor 1 ( DMRT1 ) were reported for chicken and pigeon ( Zhao et al, 2007 ; Huang et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…AS of testis-specific lactate dehydrogenase C ( LDHC ) and doublesex- and mab-3-related transcription factor 1 ( DMRT1 ) were reported for chicken and pigeon ( Zhao et al, 2007 ; Huang et al, 2012 ). NGS has been recently applied for the characterization of AS events during chicken male germline stem cell differentiation ( Sun et al, 2021 ), sex-specific aspects of the stress response in rock doves ( Lang et al, 2020 ) and the demonstration of the role of AS in the evolution of phenotypic complexity in birds ( Rogers et al, 2021 ). Nevertheless, the splicing profiles of genes involved in reproductive processes in birds have remained unexplored thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Although various alternative splicing events have been long to known to take place in both the gonad and brain, not much is known about the effects of alternative splicing on gonad development, with even lesser information about the difference in splicing between the gonad and brain. In vertebrates, various synchronous physiological events are required to regulate reproduction, and the molecular mechanism controlled by a comprehensive and interconnected biological system including the brain, the pituitary, and the gonads ( 13 ). However, information about the involvement of the HPG axis at the level of alternative splicing is limited, and even less is known about its effects at this level during testicular development.…”
Section: Introductionmentioning
confidence: 99%